1) Find a set of solutions for
"2(x-y)dx+(3x-y-1)dy=0\\\\"
"y'={2(y-x) \\above{2pt} 3x-y-1}"
Solving the system
"y_ \n0\n\u200b\t\n \u2212x_ \n0\n\u200b\t\n =0"
"3x_0-y_0-1=0"
"x_0={1 \\above{2pt} 2}, y_0={1 \\above{2pt} 2}"
We shall replace
"x=t+{1 \\above{2pt} 2}"
"y=z+{1\\above{2pt} 2}"
"y'=z'"
where t is a new independent variable, z is a new function.Substitute into equation
"z'={2(z+ {1 \\above{2pt} 2}-t- {1\\above{2pt} 2}) \\above{2pt} 3t+ {3 \\above{2pt} 2} -z- {1 \\above{2pt} 2}-1 }"
"z'={2(z-t) \\above{2pt} 3t-z}"
we shall replace
"{z \\above{2pt} t}=u(t),z=t.u. z'=tu'+u"
then,
"tu'+u={2(tu-t) \\above{2pt} 3t-tu}"
"tu'+u={2u-2\\above{2pt} 3-u}"
"tu'={2u-2 \\above{2pt} 3-u}-u"
"tu'={2u-2-3u+u^2 \\above{2pt} 3-u}"
"{3-u \\above{2pt} (u+1)(u-2)} du={dt \\above{2pt} t}"
"\\int (-{4 \\above{2pt} 3}{1 \\above{2pt} u+1}+{1 \\above{2pt} 3}{1 \\above{2pt} u-2})du=\\int {dt \\above{2pt} t}"
"-{4 \\above{2pt} 3}ln|u+1|+{1 \\above{2pt} 3}ln|u-2|=ln|t|+{1 \\above{2pt} 3} ln|c|"
"{(u-2) \\above{2pt} (u+1)^4}=ct^3 ,u+1=0"
where "u={y- {1\\above{2pt} 2}\\above{2pt} x-{1 \\above{2pt} 2} }"
The solution of the equation are
"{ {y- {1 \\above{2pt} 2}\\above{2pt} x- {1 \\above{2pt} 2} } -2 \\above{2pt}( {y- {1 \\above{2pt} 2}\\above{2pt} x- {1 \\above{2pt} 2} } )^{4}+1 }" "=c(x-{1 \\above{2pt} 2})^{3}"
"{y- {1\\above{2pt} 2}\\above{2pt} x-{1 \\above{2pt} 2} }+1=0"
2) Find a set of solutions for
"(2x+y-4)dx+(x-3y+12)dy=0\\\\ y'=-\\frac{2x+y-4}{x-3y+12}"
Solving the system
"2x_0+y_0-4=0"
"x\n_0-3y_0+12=0"
"x_0=0, y_0=4"
we shall replace
"x=t , y=z+4"
"y'=z'"
"z'=-{2t+z+4-4 \\above{2pt} t-3z-12+12}"
"z'=-{2t +z\\above{2pt} t-3z}"
we shall replace
"{z \\above{2pt} t}=u(t)" ,"z=t.u, z'=tu'+u"
then
"tu'+u={2t+tu \\above{2pt} 3tu-t}"
"tu'={2+u-3u^2+u \\above{2pt} 3u-1}"
"-{3u-1 \\above{2pt} 3u^2-2u-u} du={dt\\above{2pt} t}"
"-{1 \\above{2pt} 2}\\int {d(3u^2-2u-2)\\above{2pt} 3u^2-2u-2}du=\\int{dt\\above{2pt} t}"
"-{1\\above{2pt} 2}ln|3u^2-2u-2|=ln|t|+{1 \\above{2pt} 2}ln|c|"
"{1 \\above{2pt} 3u^2-2u-2}=ct^2"
"3u^2-2u-2=0"
where "u={y-4\\above{2pt} x}"
Then solution of the above equation are
"{1 \\above{2pt} 3( {y-4 \\above{2pt} x} )^{2}-2* {y-4\\above{2pt} x}-2 }=cx^2"
"3({y-4 \\above{2pt} x})^2-2*{y-4\\above{2pt} x}-2=0"
3) Find a set of solutions for
"\\frac{dy}{dx}=\\tan y\\cot x-\\sec y\\cos x\\\\ \\frac{dy}{dx}=\\frac{\\sin y}{\\cos y}\\frac{\\cos x}{\\sin x}-\\frac{1}{\\cos y}\\cos x\\\\ \\frac{dy}{dx}=\\frac{\\sin y\\cos x-\\sin x \\cos x}{\\sin x\\cos y}\\\\ (\\sin x-\\sin y)\\cos x dx+\\sin x \\cos y dy=0"
"put" "u=\\sin y, du=\\cos ydy"
Substituting, we get
"(sinx\u2212u)cosxdx+sinxdu=0"
"(\\sin x-u)\\cos xdx+\\sin x du=0\\\\ \\frac{du}{dx}-u\\cdot\\frac{\\cos x}{\\sin x}=-\\cos x"
The equation is first - order linear in u The integrating factor is
"I=e^{-\\int\\frac{\\cos x}{\\sin x}dx}=e^{-\\ln\\sin x}=\\frac{1}{\\sin x}\n\u200b"
Hence
"u\\frac{1}{\\sin x}=-\\int\\frac{\\cos x}{\\sin x}dx=-ln|\\sin x|+c"
solve for u
"u=-\\sin x\\ln|\\sin x|+c\\sin x"
Put y back
"\\sin y=-\\sin x\\ln|\\sin x|+c\\sin x"
Comments
Leave a comment